The ideology of managerialism in Russian social institutions: education, science, healthcare - V. V. Kovalev; A. V. Dyatlov (Вестник университета, 2023)
The article is devoted to the consequences’ study of the managerial, management tools’ use in the social institutions of science, education, and health care. The study purpose is to substantiate the thesis that managerialism is a kind of a new ideology. To achieve the presented goal, methodological tools based on D. North’s neoinstitutional theory were used. The study revealed that managerialism as an efficiency ideology is based on institutional rules accepted by the state, it is applied considering informal restrictions established in society (values, attitudes, stereotypes, behavioral patterns, etc.) and relies on the Russian bureaucracy, which is the main beneficiary of the managerialist ideology. The negative consequences of managerialism are manifested as an increase in imitative practices; a decline in the level of employees’ professionalism of scientific, health care and educational organizations; a loss of the social purpose of social institutions, and the misuse of state resources.